Thermal investigation of lithium-ion battery module with different cell arrangement structures and forced air-cooling strategies - Wang, Tao; Tseng, K.J.; Zhao, Jiyun; Wei, Zhongbao (Applied energy, 2014)
•Three-dimensional CFD model with forced air cooling are developed for battery modules.•Impact of different air cooling strategies on module thermal characteristics are investigated.•Impact of different model structures on module thermal responses are investigated.•Effect of inter-cell spacing on cell thermal characteristics are also studied.•The optimal battery module structure and air cooling strategy is recommended. Thermal management needs to be carefully considered in the lithium-ion battery module design to guarantee the temperature of batteries in operation within a narrow optimal range. This article firstly explores the thermal performance of battery module under different cell arrangement structures, which includes: 1×24, 3×8 and 5×5 arrays rectangular arrangement, 19 cells hexagonal arrangement and 28 cells circular arrangement. In addition, air-cooling strategies are also investigated by installing the fans in the different locations of the battery module to improve the temperature uniformity. Factors that influence the cooling capability of forced air cooling are discussed based on the simulations. The three-dimensional computational fluid dynamics (CFD) method and lumped model of single cell have been applied in the simulation. The temperature distributions of batteries are quantitatively described based on different module patterns, fan locations as well as inter-cell distance, and the conclusions are arrived as follows: when the fan locates on top of the module, the best cooling performance is achieved; the most desired structure with forced air cooling is cubic arrangement concerning the cooling effect and cost, while hexagonal structure is optimal when focus on the space utilization of battery module. Besides, the optimized inter-cell distance in battery module structure has been recommended.